KECEMASAN BERKOMUNIKASI PADA INTERAKSI SOSIAL ANAK USIA DINI : STUDI PADA TKK THOMAS AQUINO KELOMPOK B1 TUKA-DALUNG - Fairya Arnantika, Ni Wayan; Purnawan, Ni Luh Ramaswati; Sugiarica Joni, I Dewa Ayu (E-Jurnal Medium, 2017)
Communication Apprehension is one of the obstacles to communicating. People who experience communicate apprehension will as much as possible avoid communication situations. This research aims to know the forms of communication apprehension on early childhood and the impact of the anxiety the child communicate towards social interaction of children in her environment, so that the habit of communication apprehension children can eventually minimized. The design of this research uses qualitative research conducted at TKK Thomas Aquino B1 group with conducting observations at TKK Thomas Aquino particular observations, interview, and documentation. From the results of the study found that other forms of child’s communication apprehension among them, are not active in the activities, over communication, just silent, brooding, not excited, did not want to follow the events, depending on the teacher, did not want to run the command, crying, unwilling to be left to parents, not want to with friends, do not want to convey opinions and didn't want to talk in public. Communication apprehension on early childhood have an impact on the interaction of the child, especially in the social environment, away from the conversation with his friends, does not come into play and rarely get out of class, can‘t socialize with others and sometimes disrupt or interfere with the activities of the people in the vicinity. Keywords: communication apprehension, early childhood, impact, social interaction